Olfactory communication : chemical characterization of the preorbital secretion of the klipspringer, Oreotragus oreotragus - Yang, Tzung-Ping (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1995.